1999
DOI: 10.1152/jappl.1999.86.5.1519
|View full text |Cite
|
Sign up to set email alerts
|

Exercise V˙eand physical performance at altitude are not affected by menstrual cycle phase

Abstract: We hypothesized that progesterone-mediated ventilatory stimulation during the midluteal phase of the menstrual cycle would increase exercise minute ventilation (VE; l/min) at sea level (SL) and with acute altitude (AA) exposure but would only increase arterial O2 saturation (SaO2, %) with AA exposure. We further hypothesized that an increased exercise SaO2 with AA exposure would enhance O2 transport and improve both peak O2 uptake (VO2 peak; ml x kg-1 x min-1) and submaximal exercise time to exhaustion (Exh; m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
69
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(80 citation statements)
references
References 48 publications
7
69
4
Order By: Relevance
“…These effects have received a limited amount of research attention and the findings to date have been unclear. VO2max appears to be largely unaffected by the phase of the menstrual cycle [80,81]. However, some studies have shown increased minute ventilation [39,[82][83][84], heart rate [84][85][86] and rating of perceived exertion [84,85] during the luteal phase, which could be attributed to an increased core temperature (0.3 -0.5 °C) during this phase [84].…”
Section: 1)mentioning
confidence: 99%
“…These effects have received a limited amount of research attention and the findings to date have been unclear. VO2max appears to be largely unaffected by the phase of the menstrual cycle [80,81]. However, some studies have shown increased minute ventilation [39,[82][83][84], heart rate [84][85][86] and rating of perceived exertion [84,85] during the luteal phase, which could be attributed to an increased core temperature (0.3 -0.5 °C) during this phase [84].…”
Section: 1)mentioning
confidence: 99%
“…2 However, they found no improvements in VO2max or endurance capacity at altitude despite a small increase in oxygen saturation (3%) in the ML phase compared with the EF phase. 2 Others view an increased ventilatory response to hypoxia and hypercapnia or to exercise to be deleterious for athletic performance due to the heightened sensation of conclusions. The change in ventilatory parameters from EF to ML phase is related to the ovarian hormone concentrations.…”
Section: Introductionmentioning
confidence: 92%
“…4 However, this is not consistently reported, as a recent study did not find an increase in chemosensitivty in the mid-luteal (ML) phase compared with the early follicular (EF) phase. 2 Furthermore, an increase in body temperature is also known to elevate VE and thus the elevated body temperature associated with the luteal phase may also contribute to the observed hyperventilation. 11 The effect of elevated progesterone levels on VE during exercise remains equivocal.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations